Analysis of BOD, COD and TSS Levels in Domestic Liquid Waste (Greywater) in Households in Bada Village, Dompu Regency - Melinda, Tina; Majdi, Muhamad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Water is a very important part of life because it is used in various daily activities such as drinking, bathing, and washing. In addition, water is also used in other activities such as agriculture, animal husbandry and industry. The cause of water pollution can be caused by waste from domestic (household), industry, agriculture and others. The purpose of this study was to determine the levels of BOD, COD and TSS in Domestic Liquid Waste (Greywater) in Households in Bada Village, Dompu Regency. This study is a Qualitative Descriptive Research with sampling using the Purposive Sampling method. Sampling was carried out at the household waste outlet, with a total of 3 samples. The results of the study showed that domestic liquid waste (Greywater) has a BOD content ranging from 120.9 mg/L to 180.30 mg/L, COD content of 310.50 mg/L to 356.89 mg/L and TSS content of 98 mg/L to 115 mg/L. Based on the results of the study, the levels of BOD, COD and TSS in Domestic Waste (Greywater) in Bada Dompu Village exceed the threshold value permitted based on the Regulation of the Minister of Forestry Number 68 of 2016 concerning domestic wastewater quality standards. It is hoped that the community can process domestic liquid waste (Greywater) first before it enters the environment.